Fostering Sustainable Creativity and Innovation in Islamic Creative Organizations - Hariyadi, Bachtiar; Setyawanto, Agus; Tontowi, Tontowi (STAI Miftahul Ula Nganjuk, 2023)
One of the prominent trends in modern creative organizations is involving organizational stakeholders in idea development, promoting cooperation, sharing knowledge, and fostering creative expression. Changes in the value writing process have become essential factors in creating innovation. This research aims to analyze how innovative organizations, such as publishers, utilize their ability to manage communication channels to foster stakeholder involvement in the value writing process collectively during innovation. Through a case study approach, this research involves 25 Islamic publishers of the Indonesian Publishers Association, utilizing websites and the social network Facebook as communication tools. The research findings indicate that idea and project development, networking, collaboration, knowledge sharing, opportunities for non-formal learning, discussion platform creation, and feedback are crucial factors driving stakeholder involvement in enhancing added value in the innovation process